The putative neuraminyllactose-binding hemagglutinin HpaA of Helicobacter pylori CCUG 17874 is a lipoprotein. - O'Toole, P W (1995)
The ability of certain strains of Helicobacter pylori to cause sialic acid-sensitive agglutination of erythrocytes has been attributed to the HpaA protein (D.G. Evans, T.K. Karjalainen, D. J. Evans, Jr., D. Y. Graham, and C.H. Lee, J. Bacteriol. 175:674-683, 1993), the gene for which has been cloned and sequenced. On the basis of the hydropathy plot of HpaA and the presence of a potential lipoprotein signal sequence and modification site, and because of the similarities of these features with those of the cell envelope lipoprotein Lpp20 of H. pylori, we examined the possibility that HpaA was also a lipoprotein. Posttranslational processing of the HpaA protein expressed by the cloned gene was sensitive to globomycin, an inhibitor of the lipoprotein-specific signal peptidase II. Antibodies raised to the putative sialic acid-binding region of HpaA failed to bind to the surface of H. pylori cells in immunoelectron microscopy but instead were observed to have labeled the cytoplasm when thin sections were examined. This antibody recognized a 29,000-M(r) protein in Western blots (immunoblots) of cell extracts of H. pylori and Escherichia coli cells expressing the cloned hpaA gene. Determination of the sequence of hpaA from strain CCUG 17874 indicated significant differences from that determined by Evans and coworkers in the above-mentioned study, including extension of the gene into the open reading frame 3 downstream of hpaA to produce a protein with an M(r) of 26,414. Localization of HpaA indicated that it was predominantly located in the cytoplasmic fraction of the cell in both E. coli and H. pylori. HpaA was not observed in the sarkosyl-insoluble outer membrane fraction. An isogenic mutant generated by insertional inactivation of hpaA was unaffected in its ability to bind four different human cell lines as well as fixed sections of gastric tissue and had hemagglutination properties identical to those of the wild type. The data collectively suggest that HpaA is a nonessential lipoprotein internal to the H. pylori cell and that it is not involved in adhesion.